2019
DOI: 10.1002/joc.6126
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution climatology of drought events for Spain: 1961–2014

Abstract: This study characterizes the climatology of drought events over the mainland Spain and the Balearic Islands using high‐resolution (1.21 km2) meteorological data from 1961 to 2014. The climatology of drought was assessed based on two widely‐recognized drought indices: the Standardized Precipitation Index (SPI) and the Standardized Precipitation‐Evapotranspiration Index (SPEI), considering four different timescales (1‐, 3‐, 6‐ and 12‐months). Drought events were simply defined as sequences of months with negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 52 publications
1
17
0
3
Order By: Relevance
“…As we have aforementioned in the discussion of Figure 5, this is very reasonable, because the month in which the rogation is celebrated has less influence in the drought that trigger the rogation than the previous months. Additionally, droughts are long duration events, specifically in southwest of Spain [50].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have aforementioned in the discussion of Figure 5, this is very reasonable, because the month in which the rogation is celebrated has less influence in the drought that trigger the rogation than the previous months. Additionally, droughts are long duration events, specifically in southwest of Spain [50].…”
Section: Resultsmentioning
confidence: 99%
“…The desynchronization between pro-pluvia rogations (celebrated in the month n) and the NAO index (months n-1, n-2 and n-3) can be explained by the long average drought duration in southwest of Spain. The average duration is around 15 weeks in agricultural droughts [50]. In addition, there is a delay of one month between the NAO index and the hydrological variables in the IP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These low levels of water availability in the ponds represent a problematic situation from the point of view of their role as the main water supply for livestock, not only because of the imminent risk of supply failure, but also because water quality generally deteriorates as the water level in the ponds decreases [10,74,75], with the consequent risk to animal health. This high vulnerability to drought observed in the majority of the ponds, together with the high frequency and severity of these events in the SW Iberian Peninsula [76], questions the use of ponds as the only source of water supply in the farms. This conclusion is in agreement with the results obtained by Pulido-Fernández and Schnabel [1] in a study carried out on a large number of extensive livestock farms in the SW Iberian Peninsula, which revealed that two out of every three farms suffered occasional problems with water supply.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained the series of peaks-over-threshold (POT) using the series of drought duration and magnitude calculated at 1-, 3-, 6-and 12-month timescales. These series are stationary and do not show any trend (Domínguez-Castro et al, 2018), which is a prerequisite to apply the extreme value theory. The POT series are obtained according to a threshold (x0), as:…”
Section: Probabilistic Analysismentioning
confidence: 99%